Selling Local Modernization through the Global Corporation: Coca-Cola Bottling in Colombia, 1927-1944 (2018)
The Coca-Cola Company sold drink concentrates and licensed rights to its trademarked brands to contracted bottlers who produced and sold bottled drinks in designated geographic areas around the world, including Colombia, beginning in 1927. The franchise system enabled international expansion without large corporate growth or direct local employment allowing the company to externalize liability and financial risk. The franchise system helped the company situate the production of Coca-Cola within local economies, conscripting local elites and workers into its industry, and negotiating its representational forms to fit local contexts. The Coca-Cola Company thus benefited from the economic and political power of both the U.S. and the Colombian elite as it established its business in the country beginning in 1927. Examining print advertising from the 1920s and 1940s, the papers of Coca-Cola executives, and publications of the U.S. multinational and its Colombian franchise bottler, this article argues that The Coca-Cola Company tenuously constructed its industry, products, and brands as simultaneously global and local. While localizing the Coca-Cola industry, products, and brand, the company alluded to its modernity and global popularity, available for purchase by enterprising merchants and thirsty consumers in Colombia.